TRENDS IN EDUCATIONAL RESEARCH ABOUT LEARNING MANAGEMENT SYSTEM AS CONTRIBUTIONS IN PRIMARY SCIENCE LEARNING: A SYSTEMATIC LITERATURE REVIEW (2015-2024) - Suranti, Ni Made Yeni; Ibrahim, Ibrahim (BIOCHEPHY: Journal of Science Education, 2024)
A Learning Management System (LMS) is a platform or system designed to help manage, administer and deliver learning in an educational environment. This research aims to identify and analyze LMS research trends in their contribution to elementary school science learning in the era of revolution 4.0. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed included types of publications, publication sources, and titles of LMS research that were widely cited. The data analysis method uses bibliometric analysis assisted by VOSviewer software. The results of the study show that the LMS research trend indexed by Google Scholar from 2015 to 2024 has experienced a fluctuating increase. The most significant increase was from 2020 to 2022, then decreased in 2023. There are many documents, such as articles, proceedings, monographs, preprints, and edited books, that discuss LMS research. Keywords that are often used in LMS research are the COVID-19 pandemic, Moodle, blended learning, distance learning, Edmodo, Canvas, and others.